Nutrient optimization for indigenous microbial consortia of a Bhagyam oil field: MEOR studies - Sharma, Neha; Lavania, Meeta; Koul, Vatsala; Prasad, Dhruva; Koduru, Nitish; Pandey, Amitabh; Raj, Rahul; Kumar, M. Suresh; Lal, Banwari (Frontiers in Microbiology, 2023)
The microbial enhanced oil recovery (MEOR) method is an eco-friendly and economical alternative technology. The technology involves a variety of uncertainties, and its success depends on controlling microbial growth and metabolism. This study is one of its kinds that showed successful tertiary recovery of crude oil through indigenous microbial consortia. In this study, a media was optimized to allow the ideal microbial growth under reservoir conditions through RSM. Once nutrient recipe was optimized, the microbial metabolites were estimated through gas chromatography. The maximum amount of methane gas (0.468 mM) was produced in TERIW174 sample. The sequencing dataset showed the presence of Methanothermobacter species and Petrotoga species. In addition, these established consortia were analysed for their toxicity and they appeared to be safe for the environment. Furthermore, the core flood study showed efficient recovery that was around 25% and 34% in TERIW70 and TERIW174 samples. Thus, both the isolated consortia were appeared to be suitable for the field trials.